(3MGTjI Ydi GdOQI GdaGNQIs - (3fhQ GdOjf YHO GdQMef Hf CMeO Hf eMeO GdLGej GdfbTHfOj, GdLGej,J (B898 (3g` s
(3ChdgG (B:s
(3bhdg GdMeO ddg GdPi JLdi HPGJg dPGJg Gi Yde PGJg HPGJg dG HYde RGjO Ydi PGJg hgPG GYde Ydi hLg cdi s
(3BNQgG (B:s
(3ajecf Cf jchf GdUGOQ ChdkG HGdhLhO GdYjfi CcKQ ef hGMO ceG PgH Edjg GdUhajI GdehMOI hGddg CYde JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGHYs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B67s
(3eUOQ GbJfGA GdCUd (B:s
(3ShQjG (B(9276) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs